Comparative evaluation of caudal tramadol and fentanyl when mixed with bupivacaine in paediatric age group - Tewari, Abhinav; Singh, Ajit Kumar (International Journal of Research in Medical Sciences, 2020)
Background: A caudal block is commonly performed block for postoperative analgesia pediatric surgeries. Duration can be enhanced by addition drugs like fentanyl, tramadol, clonidine midazolam etc to local anesthetics helps in decreasing the requirement of postoperative analgesics. This study was conducted to assess the analgesic efficacy of tramadol or fentanyl when mixed with bupivacaine in pediatric patients for surgeries below the umbilicus. Methods: Fifty children of ASA I and ASA status, between 2 to 12 years of age, of both sexes underwent elective surgeries below umbilicus were selected and randomly divided into groups of 25 each. One Group, T (n = 25) received 0.75 ml/kg of 0.25% bupivacaine with tramadol 1mg/ kg and other Group F (n = 25) received 0.75 ml/kg of 0.25% bupivacaine with Inj fentanyl 1μg/kg. Assessment of analgesia and any side effects after caudal injection to the first administration of analgesia were recorded for both the groups in next 24 hours following objective pain scores. Duration of analgesia and requirement of additional rescue analgesics was noted. Results: The Mean duration of analgesia recorded longer in Group T (18.26±6.1 hours) as compared to Group F (10.0+/- 2.68 hrs.) and no significant haemodynamic changes or adverse effect noted between 2 groups. Conclusions: Addition of tramadol, 1mg/kg to bupivacaine 0.25% for caudal anesthesia in children undergoing surgeries below umbilicus, enhances and prolongs postoperative analgesia compared to caudal fentanyl 1μg/kg and bupivacaine 0.25% alone.